2017
DOI: 10.1093/pubmed/fdx115
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and smoking advice recalled by patients attending a UK age-related macular degeneration clinic

Abstract: The findings suggest that it would be beneficial to review the provision of lifestyle advice to patients attending AMD outpatients' clinics, and to consider whether advice is being provided in an optimal format for later recall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…13,[30][31][32] Of concern, a recent British study reported that only 53.1% of smokers with AMD recalled that they were advised to quit smoking by their ophthalmologist or optometrist. 33 The adjusted mean visual acuity improvement at 12 months was significantly different among the three groups. Nonsmokers had more than twice the gain in visual acuity after 12 months than smokers.…”
Section: Discussionmentioning
confidence: 83%
“…13,[30][31][32] Of concern, a recent British study reported that only 53.1% of smokers with AMD recalled that they were advised to quit smoking by their ophthalmologist or optometrist. 33 The adjusted mean visual acuity improvement at 12 months was significantly different among the three groups. Nonsmokers had more than twice the gain in visual acuity after 12 months than smokers.…”
Section: Discussionmentioning
confidence: 83%
“…Alarmingly, among those with arthritis and overweight or obesity, approximately 75% of adults with overweight and 50% of those with moderate obesity (BMI 30 to < 35) are not receiving any provider weight-loss counseling [65]. The Royal College of Ophthalmologists maintains specific lifestyle counseling criterion for age-related macular degeneration, yet patients report that physicians rarely discuss the major portions of the guidelines [66]. Evidence also indicates that whether or not a physician engages in lifestyle guidance is a product of their own belief systems; that is, regardless of existing evidence supporting the importance of lifestyle, if a physician maintains the belief that lifestyle will not affect outcomes, they are unlikely to engage in such counseling [67].…”
Section: Nutrition Lifestyle Trainingmentioning
confidence: 99%
“…In age-related macular degeneration, specific guidelines have been crafted by the Royal College of Ophthalmologists concerning smoking cessation, as well as diet and nutritional supplement advice to be given to all patients. However, a recent post-visit study of patients shows that very few recommendations were made by physicians on these three matters [78].…”
Section: Lifestyle In Training and Practicementioning
confidence: 99%